Handbook of strategic e-business management - Martinez-Lopez, Francisco J. (Progress in IS, 2014)
This research handbook provides a comprehensive, integrative, and authoritative resource on the main strategic management issues for companies within the e-business context. It covers an extensive set of topics, dealing with the major issues which articulate the e-business framework from a business perspective. The handbook is divided into the following e-business related parts: background; evolved strategic framework for the management of companies; key business processes, areas and activities; and, finally, emerging issues, trends and opportunities, with special attention to diverse Social Web-related implications.   The articles are varied, timely and present high-quality research; many of these unique contributions will be especially valued and influential for business scholars and professionals interested in e-business. Many of the contributors are outstanding business scholars who are or have been editors-in-chief of top-ranked management and business journals or have made significant contributions to the development of their respective fields.